Note on Matuzsewska-Orlich indices and Zygmund inequalities - Samko, N. (Armenian Journal of Mathematics, 2010)
In this note we call attention to the fact that there exist some relations between the Matuszewska-Orlicz indices $m(φ)$ and $M(φ)$ of the function $φ$, and possible values of the constants in Zygmund type inequalities.